The encyclopedia of drawing techniques - Harrison, Hazel (Search Press, 2010)
In this step-by-step directory of drawing techniques, detailed photographic sequences explore pencil, charcoal, pen and technical pen techniques, including shading, building up, blending, hatching, highlighting, stippling and more. Sequences on mixed media, keeping a sketchbook and digital drawing are included also